Silence, expressive and significant matter - Torras i Segura, Daniel (Anàlisi, 2015)
Significance, expression and communication need not always go together. However, audiovisual silence as a resource and for psycho-perceptive contrast can be significant. It may be a form of expression and it can be a type of communication. Audiovisual silence is significant because it is part of the world and it is perceptible; everything that is perceptible can be interpreted and make discernible sense. Similarly, it is also significant because, despite its ambiguity, it may refer to a different sense of itself. Silence is a form of expression because it is the outward exteriorization of a thought or feeling in a sensitive form, which is, once again, perceptible. The voluntariness of issue reinforces the idea of silence as an expression, and even more so in the context of an audiovisual product. Silence is communication because it is part of the message and, even when someone does not intend to say anything with a silence, it communicates. Audiovisual silence is communication because it strives to involve a third party in a sense that it carries. Despite the possible misunderstanding, audiovisual silence qualifies visual codes of its context. Rather than as a code, it is more appropriate to understand audiovisual silence as expressive material, and within the scope of the speech, rather than in the language, in the audiovisual or linguistic context.